Nasionalisme-Religius dan Cita Kepemimpinan Nasional dalam Manuskrip Sejarah Kyai Ageng Tegalsari: Religious-Nationalism and National Leadership Imagination in the Manuscript Sejarah Kyai Ageng Tegalsari - Akhlis Syamsal Qomar; Adhie Handika Restu Damara (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
Events experienced by the Indonesian people often place nationalism and religion on opposite sides. This was marked by the strengthening politicization of identity after the 2014 general election. Issues related to certain ethnicities, ideologies, and religions were used by some elite politicians to build a bad image of their political opponents. Starting from these problems, it is necessary to strengthen the understanding of religious nationalism to strengthen Indonesian nationality which is rooted in the nation's historical legacy in the past. One of these remains is manuscripts that have become a treasure of the Indonesian people. This research uses historical research methods including the heuristic stage by culturally approaching written sources in the form of several manuscripts left in the 19th century at Perdikan Ageng Pesantren Tegalsari of Ponorogo entitled